Diagnosis of periodontal disease: Literature review (Research, Society and Development, 2025)
Introduction: Periodontal disease is an inflammatory infection that affects the supporting tissues of the teeth, including gums, periodontal ligaments, and alveolar bone. It is one of the leading causes of tooth loss in adults and is associated with various systemic conditions, such as diabetes and cardiovascular diseases. Early and accurate diagnosis is essential for periodontal disease management, allowing interventions to prevent this disease progression. Objective: This study aims to gather relevant current information on the diagnosis of periodontal disease. Methodology: A literature review was conducted to collect data on the topic from PubMed and Google Scholar between 2000 and 2025. Results: The main evidence indicates that periodontal probing is one of the primary diagnostic methods alongside clinical evaluation. Technological advancements, including tomography, biological markers, and especially the classification of periodontal diseases with the identification of risk factors, complement each other to provide a more comprehensive diagnosis, developing effective strategies for treatment prevention.